LOYALTY & DISLOYALTY: SEBUAH PANDANGAN KOMPREHENSIF DALAM ANALISA LOYALITAS PELANGGAN - Darsono, Licen Indahwati (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2004)
Marketer convinced that customer loyalty is a valuable asset for the company. But, in today marketplace managing customer loyalty is a daunting task. An understanding about customer loyalty concept is prerequisiteÂ for managing customer loyalty. Customer loyalty concept best understood with the composite approach; behavioral and attitudinal approach. Composite approach could make marketer to find out loyalty category andloyalty stages of the customers, loyaltyâ€™s antecedent and manage loyalty from that antecedent. Customer satisfaction is an antecedent of customer loyalty. But, some researchers argued that satisfaction and loyalty relationships is not linear. This statement is supported by the fact in the market, satisfied customers still defect, but several dissatisfied customers donâ€™t switch. Therefore, analyzing customer loyalty required holistic view about customer loyalty, loyalty concept alone did not give marketer a comprehensive view in customer loyalty analysis. Marketers and researchers must pay attention to disloyalty.Key words: loyalty, disloyalty, satisfaction